EFFECT OF PERINEURAL ADMINISTRATION OF DEXMEDETOMIDINE WITH BUPIVACAINE VERSUS BUPIVACAINE ALONE IN ULTRASOUND GUIDED SUPRACLAVICULAR BLOCK FOR UPPER EXTREMITY ORTHOPAEDIC OPERATIONS - Khan, Maliha Khalid; Amran Hafeez,; Faheem Feroze,; Anjum Atique Tahir,; Shehzad Abbasi,; Muhammad Shaheer bin Faheem,; Saeed Farooq, (Journal of Ayub Medical College Abbottabad, 2023)
Background: During procedures on the upper limbs, the brachial plexus block is usually advised. To increase the length of the block, many medicines have been utilized as adjuvants. The purpose of this study was to compare the effects of dexmedetomidine plus bupivacaine against bupivacaine alone on the onset and duration of the sensory and motor block and the duration of analgesia in the supraclavicular block during upper extremity orthopaedic surgery. Methods: Sixty individuals qualified for orthopaedic operations on the upper extremities, ranging in age from 20 to 60 years, participated in this prospective, randomized investigation. The modified Bromage scale and the pinprick method were used to assess the sensory and motor block. Using a visual analogue pain scale, the postoperative pain was evaluated at 0, 6, 12 and 24 hours after surgery. Results: In patients receiving only bupivacaine, the mean onset time of sensory and motor block was 32.84 minutes and 26.67 minutes respectively; while in those receiving bupivacaine along with dexmedetomidine, it was 23.38 minutes and 14.81 minutes (p<0.005). In the intervention group (bupivacaine and dexmedetomidine), the period between the first request for analgesia and the duration period of sensory and motor block were both longer (p<0.005). The intervention group experienced less postoperative discomfort for 24 hours (p<0.05). Conclusion: Dexmedetomidine added to bupivacaine perineurally prolonged both numbness and immobility while shortening the time it took for sensory and motor blocks to begin. Moreover, dexmedetomidine considerably decreased postoperative pain when combined with bupivacaine for supraclavicular blocks.